PARALLEL PRICING AND THE USE OF CIRCUMSTANTIAL EVIDENCE IN PROVING PRICE-FIXING CARTELS - Hesty Diyah Lestari (Veritas et Justitia, 2025)
Most jurisdictions rely on indirect (circumstantial) evidence to prove parallel pricing that constitutes a price-fixing cartel when there is no direct evidence of an agreement among competing businesses. In Indonesia, however, the use of circumstantial evidence in proving price-fixing cartels remains debatable, as the Competition Act does not explicitly recognize circumstantial evidence as a form of proof available to the Business Competition Supervisory Commission (KPPU) in enforcing the Act. In several price-fixing cases, courts have rejected KPPU decisions that relied solely on circumstantial evidence to establish the existence of an agreement. This article examines how circumstantial evidence has been applied by the KPPU and the courts in cases involving parallel pricing. It further analyzes whether the Competition Act accommodates circumstantial evidence as a valid means of proving parallel pricing that amounts to a price-fixing cartel. The article seeks to clarify the significance of circumstantial evidence in establishing price-fixing agreements, which is essential for effective enforcement of competition law in Indonesia. Based on normative legal research, the article concludes that the use of circumstantial evidence in prosecuting price-fixing cartels can be justified under the existing Competition Act.